2019
DOI: 10.1002/cctc.201900401
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Synthesis from CO2 Hydrogenation

Abstract: In the future we will be phasing out the use of fossil fuels in favour of more sustainable forms of energy, especially solar derived forms such as hydroelectric, wind and photovoltaic. However, due to the variable nature of the latter sources which depend on time of day, and season of the year, we also need to have a way of storing such energy at peak production times for use in times of low production. One way to do this is to convert such energy into chemical energy, and the principal way considered at prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
176
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(182 citation statements)
references
References 44 publications
(60 reference statements)
4
176
0
2
Order By: Relevance
“…Pd possesses the ability to activate hydrogen gas into H‐adatoms that can spillover unto metallic oxide supports and in the presence of CO (originated from dissociative adsorption of CO 2 ) form a formate ion which can be further hydrogenated to methanol or methane . The simplest example is Pd supported on ZnO and reduced with temperature >∼300 °C which results in the formation of the 1 : 1 PdZn alloy that shows very good selectivity to methanol . From the computational point of view this shows that DFT calculations are very necessary in studies of transition metals and bimetallic systems.…”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd possesses the ability to activate hydrogen gas into H‐adatoms that can spillover unto metallic oxide supports and in the presence of CO (originated from dissociative adsorption of CO 2 ) form a formate ion which can be further hydrogenated to methanol or methane . The simplest example is Pd supported on ZnO and reduced with temperature >∼300 °C which results in the formation of the 1 : 1 PdZn alloy that shows very good selectivity to methanol . From the computational point of view this shows that DFT calculations are very necessary in studies of transition metals and bimetallic systems.…”
Section: Current Understanding Of Co2 Catalytic Hydrogenationmentioning
confidence: 99%
“…[42] The simplest example is Pd supported on ZnO and reduced with temperature >~300°C which results in the formation of the 1 : 1 PdZn alloy that shows very good selectivity to methanol. [148] From the computational point of view this shows that DFT calculations are very necessary in studies of transition metals and bimetallic systems.…”
Section: Catalysts Used In Methanol Synthesismentioning
confidence: 99%
“…“Greenhouse effect” caused by the emission of CO 2 has led to climate changes and increasing temperatures globally within the past decades and thus a major imperative for the 21 st century will be to reduce the concentration of CO 2 in the atmosphere. A net‐zero‐carbon fuel economy may be realized if it efficiently utilizes CO 2 to produce carbon‐based fuels such as alcohols, hydrocarbons and formic acid (FA) [1–20] . Among these, FA is an attractive product that can be easily generated via CO 2 hydrogenation reaction, which exhibits wide applications in leather tanning, silage preservation and hydrogen storage [21–23] .…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies have been reported dealing with the reaction kinetics and mechanism over CZA-based materials, and several models have been proposed to explain the experimental results [6][7][8][9]. However, there is still debate regarding the reaction mechanism and catalyst requirements [4,10,11]. As far as catalysts are concerned, efforts have been made to improve the performance of CZA by either replacing/doping Cu with noble metals (e.g., Pt, Pd) [12][13][14][15] or by adding oxides in order to enhance the adsorption properties of the support and to increase the dispersion of the Cu phases [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%